Praktik Pembakaran Sampah Rumah Tangga dalam Perspektif Sosiologi Kesehatan: Antara Rasionalitas Praktis dan Keterbatasan Struktural di Desa Pusakamulya - Arini Puspa Wardani; Nazwa Fatin Oktaviani; Muhammad Aldi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the practice of household waste burning in Pusakamulya Village from a sociological perspective, emphasizing the relationship between the community's practical rationality and the structural limitations surrounding it. Household waste is a growing environmental issue in Indonesia, where the household sector contributes more than half of the total national waste generation, but much of it is not optimally managed (SIPSN, 2025). Under these conditions, open waste burning remains a common practice among rural communities because it is considered the easiest, quickest, and cheapest way to reduce waste accumulation (Mustafa et al., 2025). This study used a qualitative approach with a case study method, through data collection techniques such as observation, in-depth interviews, and documentation with the community, village officials, health cadres, and community leaders. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and conclusion drawing (Miles et al., 2019). The analytical framework uses a sociological perspective of health, integrating Pierre Bourdieu's concept of habitus, Anthony Giddens' structuration, and Ulrich Beck's concept of risk society. The results of the study indicate that the practice of waste burning is driven not only by habit or low environmental awareness, but also by significant structural limitations, such as the lack of a regular waste collection system, weak waste bank institutions, and a lack of integrated waste management facilities. These conditions leave communities with limited options, making burning waste a practical rationality considered the most feasible in everyday life (Bourdieu, 1990; Azkiyah, 2026).